2009
DOI: 10.1038/bmt.2009.299
|View full text |Cite
|
Sign up to set email alerts
|

CsA exposure is associated with acute GVHD and relapse in children after SCT

Abstract: CsA is commonly used after haematological SCT (HSCT) as GVHD prophylaxis. In solid organ transplantation, area under the blood concentration vs time curve (AUC) correlates with clinical outcome. However, in HSCT, it has not been determined whether the AUC is superior to trough level monitoring to optimize clinical efficacy of CsA therapy. Therefore, the aim of this study was to investigate the relationships between CsA trough levels and/or AUC early after HSCT with clinical outcome. A total of 91 children (1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…[8][9][10] It is now generally agreed that CsA trough blood concentration (TBC) is the pharmacokinetic parameter that best correlates with GvHD outcome. 11,12 Nevertheless, there are no data regarding specific values of CsA TBC to target to favor mild aGvHD without increasing the incidence of severe GvHD. Based on our previous experience, we have been performing therapeutic drug monitoring of CsA TBC combined with Bayesian dose adjustment, and targeting relatively low levels in leukemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] It is now generally agreed that CsA trough blood concentration (TBC) is the pharmacokinetic parameter that best correlates with GvHD outcome. 11,12 Nevertheless, there are no data regarding specific values of CsA TBC to target to favor mild aGvHD without increasing the incidence of severe GvHD. Based on our previous experience, we have been performing therapeutic drug monitoring of CsA TBC combined with Bayesian dose adjustment, and targeting relatively low levels in leukemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 It has also been suggested that monitoring CsA exposure early after hematological SCT and adjusting the CsA dose accordingly may provide a tool to affect GVHD/GVL (graft-versus-leukemia) balance. 25 AUC monitoring can be more feasible by using an LSS that allows AUC to be estimated using a small number of blood samples collected at specific time points .A few reports are available on defining LSSs for the determination of cyclosporine systemic exposure (AUC) in bone marrow transplant patients. 5,11,26,27 In an attempt to find the best single time point for the monitoring and adjusting of CsA dose using twice-daily 3-hour intravenous infusions in allogeneic hematopoietic SCT, Furukawa et al 26 concluded that c 2 h and c 3 h correlated best with AUC 0-12 h .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, monitoring cyclosporine and tacrolimus exposure early after HSCT and adjusting their doses to a prdefined target trough levels and areas under the blood concentration versus time curve may provide a tool to influence GVHD/GVL (graft versus leukemia) balance and clinical outcome. [27][28][29] Imatinib can also interfere with the metabolism of cytotoxic drugs like cyclophosphamide by competing for metabolization by cytochrome P450-3A4. One potential result of such drug interactions could be a higher incidence of extra-medullary toxicities after myeloablative conditioning therapy.…”
Section: Discussionmentioning
confidence: 99%